Electrochemical Performances of NMC811 Lithium-Ion Pouch Cells under Dynamic Conditions - Mahmud Tokur (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Lithium-ion batteries have a wide range of usage areas, from transportation to the defense industry, from daily usage to space applications. The widespread use of consumer electronics day by day also increases the need for this critical strategic technology, which allows us to live at almost every point of our lives without binding factors such as cables. But this technology also has many limitations, which dominate our lives so much that it needs to be overcome. Low cycle life due to poor electrochemical efficiency of electrode materials is one of these limitations. At the same time, energy density constraints are also an obstacle to many technological developments. Therefore, finding new materials with higher capacity and higher cycle life has become inevitable to meet the demands. Moreover, developing novel production techniques suitable for the materials used in the battery is also critical. Cylindrical cells are mostly used commercially in the market due to their easy and fast production technics and relatively safe components. However, the energy density and capacity limit of this architecture pushes the market to use alternative cell designs. There are different cell structures in the lithium-ion battery industry apart from cylindrical cells, such as button type, pouch type, and prismatic type. Among them, pouch cells have rising star geometry due to their unique properties and flexible production style. But many parameters still need to be overcome in pouch cells. In this study, the NMC811 cathode has been selected to investigate some critical parameters in lithium-ion pouch cells. The effects of dynamic conditions such as electrode film thickness, variable temperatures, and current rates on electrochemical performance were analyzed. Finally, a cycle life test was performed on the cell with optimum parameters.